Key photovoltaic parameters of organohalide lead perovskite quantum dot intermediate band solar cell: A numerical investigation. (December 2021) - Roy, Sourav; Mondol, Nibir; Hossain, Md. Sanwar; Howlader, Ashraful Hossain; Hossain, Md. Jubayer; Islam, Md. Rafiqul; Sarkar, Animesh
Abstract: In this work, a p-i-n junction type intermediate band solar cell (IBSC) model based on metal halide perovskite nanocrystals, specifically methylammonium lead iodide (MAPbI3 ) quantum dot (QD) and methylammonium lead bromide (MAPbBr3 ) barrier is designed analytically for the revolutionary next-generation photovoltaic applications. TiO2 and Spiro-OMeTAD are considered as transport layer for electron and hole, respectively. The impact of QD size and dot spacing on the key parameters of MAPbI3 QD-IBSC is illustrated by showing the wave nature of charge carriers within the QDs and their barrier. In order to identify the number of miniband in a single regime, Schrödinger equation is solved as a function of host energy gap using Kronig–Penney model. From the characteristics of electronic wave functions, it is evident that varying the QD size and interdot spacing lead to formation of more than one IB. For any case, (100)-oriented fcc crystal lattice structure is assumed. Major performance indicators of the device such as photocurrent intensity Jsc, open circuit voltage Voc, fill factor, absorbance spectra, photoluminescence (PL) intensity, external quantum efficiency (%EQE) and power conversion efficiency (PCE) η have been delineated. Highest PCE of 26.03% is attained for QD size of 5 nm and interdot spacing of 0.5 nm under one sun and AM 1.5 solar irradiation. Graphical Abstract: ga1 Highlights: Analytical modeling of organolead halide perovskite quantum dot intermediate band solar cell (QD-IBSC). Photo-absorber consists of MAPbI3 QDs embedded within MAPbBr3 barrier in order to raise photon absorption via IBs. Major performance indicators of the device such as Jsc, Voc, FF, %EQE and PCE have been delineated. Highest PCE of 26.03% is attained for QD size of 5 nm and dot spacing of 0.5 nm under one sun and AM 1.5 solar irradiation. The spectral response shows remarkable rise in %EQE by hybridizing MAPbI3 QDs within host band gap due to formation of 3 IBs.